RANCANG BANGUN PERANGKAT PEMANTAU CUACA OTOMATIS BERBASIS MIKROKONTROLER PADA JARINGAN WLAN IEEE 802.11b - Sucipto, Willy; Djuni Hartawan, i. G. A. K. Diafari; Setiawan, Widyadi (Jurnal SPEKTRUM, 2018)
This research intends to build an automatic weather monitoring device based on microcontroller that can monitor changes in temperature, humidity, air pressure, wind direction and velocity through the sensors that have been placed on the weather monitoring location. The flexibility of this weather monitoring tool is intended to allow weather forecaster operators to monitor weather and process data from anywhere. To increase the flexibility of the sensor data processed on wemos microcontroller will be connected with access points in 2.4 GHz wireless network, then the data will be sent to the web server. Sensor data in addition to sent to the internet will also be stored on the SD Card as a data backup system in the form of data loggers. The device test results state that the tool has been operating properly and can be used to monitor the weather.